Effects of yeast culture on growth performance, immune function, antioxidant capacity and hormonal profile in Mongolian ram lambs - Chen, Hui; Liu, Shixiong; Li, Songjian; Li, Dongfang; Li, Xueqiang; Xu, Zixuan; Liu, Dacheng (Frontiers in Veterinary Science, 2024)
As effective growth-promoters and immune-modulators, yeast fermented products have shown positive effects in ruminants. To explore the mechanisms of yeast culture promoting growth and regulating immunity, this study investigated the effects of yeast culture, and β-glucan as one of its main active ingredients, on the growth performance, immune function, antioxidant capacity and hormonal profile in Mongolian ram lambs. One hundred and five Mongolian ram lambs were randomly assigned to 3 groups, with 35 replicates in each group. The dietary treatments were: total mixed ration (TMR) as the control group, TMR supplemented with 50-70 g/kg yeast culture (YC) or 75 mg/kg β-glucan. The test period was 137 days. All the sheep were weighed and 6 serum samples were collected in each group on days 0, 30, 60, 90 and 130, respectively. The results showed that both YC and β-glucan could promote the growth performance with increased average daily gain and decreased feed to weight gain ratio. Moreover, these two feed additives facilitated the immune function by selectively increasing the serum levels of lysozyme, IgG, IgM, INF-γ, TNF-α and some interleukins (IL-1β, IL-2, IL-6 and IL-8); ameliorated the antioxidant capacity with higher total antioxidant capacity and enzyme activities of catalase and glutathione peroxidase; altered the metabolism-associated hormone levels with higher growth hormone and thyroid hormone T3 but lower cortisol and insulin. In conclusion, both YC and β-glucan could improve the growth performance, immune function and antioxidant capacity, and regulate the serum levels of metabolismassociated hormones, thus exerting effects of promoting growth and improving immune function. Therefore, YC could be considered as a suitable potential alternative strategy to antibiotics and be used as an animal feed additive. This article provides a theoretical basis for the clinical application of such yeast fermented preparations in mutton sheep husbandry.